Performance of hair sheep in Nigeria - Dettmers, A. (Winrock International, 1982)
West African Dwarf sheep are the indigenous sheep in the humid tropics of Nigeria. They are similar to the forest Djallonke sheep in the other West African countries. Ewes are non seasonal and can produce three crops in two years. They are early maturing, show good fertility, and have high prolificacy (multiple births). However, in spite of their adaptation, mortality rates are high. Most sheep are maintained under extensive management condtions. Supplementation has increased growth rates, even though these sheep are small with one-year weights of about 17 kg. These sheep yield fair carcass with over 40% yield. Among sheep of the arid zone, Uda and Yankasa of northern Nigeria are described. The Yankasa is generally superior to the Uda and to the West African Dwarf sheep, especially in reproductive performance.